USAGE OF ACTIVE METHODS OF TRAINING IN THE PROCESS OF TEACHING THE COURSE “COMPARATIVE PEDAGOGY” - Binytska К. (Continuing Professional Education: Theory and Practice, 2023)
In the article special attention is concentrated on the peculiarities of using active methods of training when teaching the course “Comparative Pedagogy” for the correspondence students of speciality “Primary Education” of Khmelnytskyi Humanitarian-Pedagogical Academy. The author analyzed the scientific works of the modern researchers on the mentioned issue. The features and advantages of using active methods of training in the work with the students of senior courses have been determined. The key peculiarities of realization of active methods of training, in particular conception of joint activity of students have been studied. It is stressed that one of the directions of perfection of the process of training primary school teachers is introduction of active methods, to which belong game forms and active methods of lessons conducting. Active methods have their characteristic features: they effectively stimulate both students’ and teacher’s activity; they are highly effective; they are many and they are varied. In the article the examples of using active methods of training when teaching the discipline “Comparative Pedagogy” have been offered, namely: brain storming, microphone, purpose-oriented groups, world café. The problems, which appear while using active methods of training students have been mentioned, namely: lack of ability to listen to other people, absence of desire to express the thought in the process of discussion, to compromise and take into consideration other people’s thoughts; passive perception of the educational material; the habit to work following the teacher’s instructions and inability to work under the conditions of uncertainty and absence of clear algorithm of actions; it is difficult for students to be mobile; students-leaders try “to draw” the group forward, when weaker students become passive at once and others.